Pemanfaatan Teknologi dalam Pengelolaan Keuangan Santri Melalui Penggunaan Software Akuntansi dan Voucher Belanja di Pesantren - Rizal Fahlefi; Muhammad Deni Putra; Alimin Alimin; Widi Nopiardo (ITB AAS INDONESIA Surakarta, 2022)
The problem that underlies this research is that at the Ulul Albab Modern Islamic Boarding School for Famales, Koto Baru, Dharmasraya Regency, West Sumatra Province, financial management is still manual and resources in the field of information technology are also lacking. Therefore, Ulul Albab uses financial applications to streamline the financial management of students and implements a shopping system using an integrated voucher application system. This study aims to explore the use of technology in the form of accounting software and shopping vouchers in managing the finances of students at Ulul Albab. The research uses the qualitative method and case study approach. The results showed that Ulul Albab utilizes existing technology to assist in the financial management of students. The